Effectiveness of Mediterranean diet on daytime sleepiness among individuals with type 2 diabetes mellitus in Oman - Salim AlAufi, Najwa; Chan, Yoke Mun; Chin, Yit Siew; Ahmad, Norliza; Mohd-Yusof, Barakatun Nisak; Waly, Mostafa I; Al Busaidi, Noor; Al-Shuriqi, Sulaiman; Al Amri, Khadija; Al Bulushi, Fatma; Al Bulushi, Sajda (Brazilian Association of Sleep and Latin American Federation of Sleep Societies, 2024)
Background Sleep disturbance is a major complaint among individuals with diabetes mellitus and may be augmented by dietary interventions. The objective of this randomized controlled trial was to determine the effectiveness of a Mediterranean diet intervention on daytime sleepiness among individuals with type 2 diabetes mellitus (T2DM) in Oman. Methods In total, 134 eligible individuals with T2DM (61 and 73 participants in the intervention and control groups, respectively) were recruited. The intervention participants underwent a 6-month Mediterranean diet intervention consisting of individual dietary counseling, cooking classes, phone calls, and social media messages, while the control group continued with standard diabetes care. Daytime sleepiness was assessed using the Epworth Sleepiness Scale. All data was analyzed using IBM SPSS Statistics for Windows, version 26.0 (IBM Corp., Armonk, NY, USA). Results Daytime sleepiness was evident, with ∼ 30% of the participants experiencing it, with no significant difference between control and intervention participants at baseline. There was a significant reduction in daytime sleepiness in both the intervention and control groups after 6 months, with daytime sleepiness significantly lower in the intervention group, with a modest difference of 42.56% (p < 0.001). Conclusion Adherence to the Mediterranean diet is effective in reducing daytime sleepiness among individuals with T2DM. © 2024. Brazilian Sleep Association. All rights reserved.